Influence of Arctic Microlayers and Algal Cultures on Sea Spray Hygroscopicity and the Possible Implications for Mixed-Phase Clouds - Christiansen, Sigurd; Ickes, Luisa; Bulatovic, Ines; Leck, Caroline; Murray, Benjamin J.; Bertram, Allan K.; Wagner, Robert; Gorokhova, Elena; Salter, Matthew E.; Ekman, Annica M.L.; Bilde, Merete (Journal of Geophysical Research: Atmospheres, 2020)
As Arctic sea ice cover diminishes, sea spray aerosols (SSA) have a larger potential to be emitted into the Arctic atmosphere. Emitted SSA can contain organic material, but how it affects the ability of particles to act as cloud condensation nuclei (CCN) is still not well understood. Here we measure the CCN-derived hygroscopicity of three different types of aerosol particles: (1) Sea salt aerosols made from artificial seawater, (2) aerosol generated from artificial seawater spiked with diatom species cultured in the laboratory, and (3) aerosols made from samples of sea surface microlayer (SML) collected during field campaigns in the North Atlantic and Arctic Ocean. Samples are aerosolized using a sea spray simulation tank (plunging jet) or an atomizer. We show that SSA containing diatom and microlayer exhibit similar CCN activity to inorganic sea salt with a κ value of ∼1.0. Large-eddy simulation (LES) is then used to evaluate the general role of aerosol hygroscopicity in governing mixed-phase low-level cloud properties in the high Arctic. For accumulation mode aerosol, the simulated mixed-phase cloud properties do not depend strongly on κ, unless the values are lower than 0.4. For Aitken mode aerosol, the hygroscopicity is more important; the particles can sustain the cloud if the hygroscopicity is equal to or higher than 0.4, but not otherwise. The experimental and model results combined suggest that the internal mixing of biogenic organic components in SSA does not have a substantial impact on the cloud droplet activation process and the cloud lifetime in Arctic mixed-phase clouds.